Perancangan Sistem Informasi Sekolah Berbasis Web Pada Paud Qur’an Nurul Ikhlas Cipayung - Widya Puspita Cahyani; Ananda Safitri; Muhammad Agung Prasetio (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
In today's digital age, all aspects of human life are now inseparable from technological developments including websites as information media. At PAUD Qur'an Nurul Ikhlas Cipayung itself still uses Brochures to market information services about the School, prospective parents of students also have difficulty getting school information related to services and facilities at PAUD Qur'an Nurul Ikhlas Cipayung, To overcome these problems, a website was designed for PAUD Qur'an Nurul Ikhlas Cipayung which is used as an information system that can be accessed by users or prospective parents of students widely, and is useful for PAUD Qur'an Nurul Ikhlas Cipayung as a more structured information data management. The approach taken by the authoris by observation and interview. The results of this study resulted in the design of a website-based information system at PAUD Qur'an Nurul Ikhlas Cipayung which makes it easier for prospective parents of students to see all services, facilities and school information available at PAUD Qur'an Nurul Ikhlas Cipayung, and can facilitate the PAUD Qur'an Nurul Ikhlas Cipayung Admin in information data management.